0052 Organising A Multispecialty Team Building Day Based On Simulated Obstetric Crisis Scenarios. (1st November 2014) - Paul, Varghese; Khoo, Charity; Kaskos, Husam; Loudon, Jenifer; Kayani, Rahim
Abstract : Background: Obstetric emergencies are highly stressful and intense time-pressured situations. The team involved consists of Obstetricians, Midwives, Anaesthetists and other healthcare staff brought together for that instant. Awareness of local protocols and good teamwork is critical for a successful outcome. This identified the need to provide training in team building for this multispecialty team which had to come together at such short notice. Methodology: An acceptable date was fixed and the conduct of the day finalised via emails and small group meetings. The venue was chosen as the postgraduate centre lecture theatre. The day was named SimMOA (Simulation for Midwives Obstetricians and Anaesthetists). The plan included starting the day with lectures highlighting the importance of simulation based teaching in healthcare and working together in teams. This would be followed by 4 simulation scenarios on obstetric emergency topics. The candidates would be divided into 4 groups. Each would participate in one scenario while the others acted as observers. The groups would be debriefed separately with focus on working in teams and reflection on individual performances. This would be followed by a presentation on the clinical aspects of that topic. Results: The venue was set-up with the simulation equipment and other props: caesarean kits, anaesthetic machine, defibrillator, theatre dresses, etc. 12 faculty and 60 candidates attended. The scenarios were well enacted. The debrief sessions had enthusiastic and animated discussions. Candidates found the clinical talks informative and welcomed the hand-outs. Conclusions: The simulated environment (a novelty for many) provided a safe platform for learning and team building. Take home messages included:- awareness of the importance of communication in team working, knowing ones limitations, timely calling for help, situational awareness, listening to other team members and speaking up. Recommendations: Based on extremely positive feedback, SimMOA has now been made a regular event. References: Issenberg SB. The Scope of Simulation-based Healthcare Education. Simulation in Healthcare 2006;1(4) Weller JM, Nestel D, Marshall SD, et al . Simulation in clinical teaching and learning; Med J Aust 2012;196(9):594 Beaubien JM, Baker DP. The use of simulation for training teamwork skills in health care: how low can you go?; Qual Saf Health Care 2004;13(Suppl 1):i51–6